BRIGID BROPHY avant-garde writer, critic, activist - Canning, Richard; Kember, Gerri (EDINBURGH UNIV PRESS, 2020)
This book explores all aspects of Brophy's literary career, alongside contributions on animal rights, vegetarianism, anti-vivisectionism, humanism, feminism and sexual politics, not only celebrating Brophy's eclectic achievements but fully reflecting them.